Physiotherapy Management For Pedicled Ld Flap And Stsg E.C Soft Tissue Tumor : A Case Report - Kamela Afrelia; Mahendra Wahyu Dewangga; Nilam Nur Hamidah (Pusat Riset dan Inovasi Nasional, 2024)
Background: Pedicled LD Flap and STSG are reconstructive measures to cover defects in extensive tumor conditions in the brachii region, especially the elbow. In this case, physiotherapy management is given to accelerate recovery to be more optimal, reduce the risk of complications and improve functional results in the brachii region. Methods: In this study using the Case report method conducted at Prof. Dr. I.G.N.G Ngoerah Bali Hospital in a male patient aged 15 post Pedicled LD Flap and STSG with complaints of pain in the surgical scar area, limited joint motion, and impaired functional ability. Given exercise, infrared modality, and ADL training with 1x a week for 2 weeks. Results: Overall there was an increase in sinistra AGA muscle strength, increased joint motion scope, and improved functional ability with the SPADI Index. Conclusion: Based on research using this case report, it shows that physiotherapy management in post Pedicled LD Flap and STSG E.C Soft Tissue Tumor conditions given infrared, exercise, and ADL training can be concluded to be able to reduce pain, reduce stiffness, increase the scope of joint motion, increase muscle strength, and improve joint functional abilities and daily activities of patients.